PENGARUH FASILITAS KERJA TERHADAP KEPUASAN KERJA ASN DINAS SOSIAL DAN PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN KEPULAUAN MENTAWAI - Yulidarni Yulidarni; Siti Osa Kosassy; Yull Hartono (Jurnal Public Administration, Business and Rural Development Planning, 2021)
This study aims 1). This is to find out how big the level of work facilities is given to ASN, P3A Social Service, Mentawai Islands Regency. 2). This is to find out how much the job satisfaction level of the ASN Social Service Office for the Social Affairs of the Mentawai Islands Regency. 3) To find out how the effect of work facilities on the job satisfaction of ASN Social Service Office of Social Affairs, Mentawai Islands Regency? This study uses a quantitative method of facilities as the independent variable and job satisfaction as the dependent variable. The sample in this study were all employees who work at the Social Service for Women's Empowerment and Child Protection. A total of 32 people. The statistical method uses simple analysis, by testing the hypothesis t test. Based on the results of this study, the following conclusions were obtained: 1). Based on the results of the questionnaire that researchers have distributed, the facility level is 8.76 with the Total Respondent Achievement (TCR) of Facilities is 72.92% which is at 65% - 79.99% with good enough criteria. This means that the Respondent gives a fairly good assessment of facilities, facilities are very much needed in completing a job or a problem faced by an employee. Because facilities are one of the factors that support the development or failure of job satisfaction results. 2). The level of job satisfaction at the Social Service for Women Empowerment and Child Protection Based on the results of the questionnaire that researchers have distributed, the average score for the Job Satisfaction Variable is 9.21 with the Total Respondents' Achievement (TCR) is 70.83% which is at 65% -79.99% with good enough criteria. This means that the respondent gives a pretty good assessment of job satisfaction. A result of job satisfaction can be seen through the quality and quantity of work achieved by someone in carrying out their duties according to their responsibilities. There is a positive effect of Facility Variables on Job Satisfaction Variables at the Social Service for Women's Empowerment and Child Protection. 3). Based on the results of statistical calculations for the Facility Variable, the value of tcount> ttable is 5.100> 2.021 with a significance result of 0.007 <0.05, this illustrates that there is a significant effect of facilities between Facility Variables on Employee Satisfaction Variables. By using a one-way test in order to get the results Ho rejected Ha accepted. Where the regression equation model is Y = 17,637 + 0.545 X. This shows the effect of a facility on employee job satisfaction. In other words, the higher the facility level of an employee, the better the results of work satisfaction.